Hocalı Faciasının Azerbaycan Ekonomisine Tesiri - Rüstemov, İlham (Fırat University, 2013)
İnsanlık dramı ve asrın katliamı olarak adlandırılan Hocalı faciası Azerbaycan halkının yakın tarihte yaşadığı en ağır hadiselerden biri ve 26 Şubat 1992’de bir şehrin yerle bir olduğu çocukların ihtiyarların gaddarca öldürüldüğü dehşetli bir facianın tarihidir. Bu makalede Hocalı faciasının ağır ve acı neticeleri ile birlikte ekonomik tesirleri tahlil olunmuştur. Ayrıca Hocalı’da sosyo-ekonomik yapının mahvedilmesi, tarih ve kültür eserlerine zarar verilmesinin Azerbaycan’ın turizm sektörünün gelişmesine verdiği büyük zarar incelenmiştir

The Khojaly tragedy- one of the greatest human carnage in twentieth century is the most important and cruelest violence that Azerbaijani nation faced so far. February 26, 1992 is the date of the tragedy when one city was entirely destroyed, children and old people were killed with great cruelty. Besides the painful results of this violent crime, economic aspects are also tried to be analyzed in this article. The great damage to the development of Azerbaijan tourism sector is also highlighted as a result of devastation of social and economic infrastructure, and destruction of the historical and cultural monuments in Khojaly
The Impact of the Economy of the Khojaly Tragedy